Alkylthio-tetrasubstituted Lu(III) phthalocyanines: Effect of the substituent bulkiness and length on their photophysical, photochemical, electrochemical and sensing properties - Albakour, Mohamad; Celik, Gizem Gumusgoz; Yaseen, Aymen Nabeel; Sen, Zafer; Dumoulin, Fabienne; Harbeck, Mika; Isci, Uemit (Elsevier, 2025)
Four monomeric Lu(III) phthalocyanines peripherally substituted with either butyl substituents of different bulkiness (n-, iso or tert-butyl) or n-hexadecyl substituents have been synthesized and characterized by FT-IR, 1H NMR, UV-vis spectroscopy and mass spectrometry. The effect of the substituents bulkiness or chain lengths on their photophysical, photochemical and electrochemical properties has been evaluated with a structureproperties relationship approach. Finally, because of an ongoing interest in the development of new volatile organic compounds sensing layers, their gas sensing properties using quartz crystal microbalance (QCM) have been studied, with insights on the influence of the substituents on the analyte sorption and QCM sensing properties.
Keywords: Phthalocyanine; Lutetium(III) phthalocyanine; Chemical sensor; Volatile organic compound (VOC)